Implementation of Village Fund Allocation Policy in Sesayap Hilir Sub-district, Tana Tidung Regency - Denny Christiyantho Denny; Agus Joko Purwanto; Ayuning Budiati (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
The village fund allocation policy is a crucial initiative in advancing rural areas. This policy must be implemented effectively to achieve its intended goals. The implementation of the village fund allocation policy involves a series of steps and processes that engage various stakeholders. Edward III emphasized that the primary issue in public administration lies in the lack of attention to policy execution. Policy implementation is critical because, without proper execution, the policy objectives cannot be achieved, and its potential positive impact on society is lost. The government of Tana Tidung Regency strives to enhance rural development and community welfare through the village fund allocation policy, regulated under Regent Regulation No. 58 of 2021. This policy reflects the regional commitment to supporting national policies as outlined in Law No. 6 of 2014 concerning Villages. This study aims to analyze the implementation of the village fund allocation policy in Sesayap Hilir District, in accordance with Tana Tidung Regent Regulation No. 58 of 2021, using variables from Edward III's theory: communication, resources, disposition, and bureaucratic structure. The research employs a qualitative descriptive method. Data analysis techniques include documentation and interviews, with interview results processed using NVivo software. To ensure more accurate and reliable findings, the triangulation method is applied. The findings indicate that, in general, the village fund allocation policy has been well and effectively implemented by policy executors, despite some challenges related to resources. Effective communication, adequate resource support, positive disposition, and a clear bureaucratic structure all contribute to the successful implementation of the village fund allocation policy in Sesayap Hilir District